German Venture Capital Market — Investments and Framework - Seyer Shafie; Matthias Liedtke; Reza Asghari (Wirtschaftsdienst)
Abstract Innovative start-ups are characterised by a high level of risk for several reasons. Venture capital (VC) enables start-ups to develop their ideas into innovations and lowers the risk of failure. This form of financing is an essential component in the global competition. This paper aims at examining the German VC market with regard to its investments and framework conditions. The framework conditions that influence VC transactions are, on one end of the spectrum, the political and regulatory environment and, on the other, the innovation climate such as societal attitudes towards entrepreneurial and opportunity risk. The paper concludes with some important policy implications.